The Issues of Academic Literacy in Conversation Practice During Online Learning - Arjulayana Arjulayana; Rachmi Rachmi (Universitas Hamzanwadi, 2022)
University students are required to be more independent in the learning process, this is because university students already have greater responsibilities, both in terms of following the campus’ rules where they study, as well as in terms of discipline in doing assignments as students. Low academic literacy will result in not achieving responsibilities and learning objectives, campus facilities, student abilities, and lecturer competencies. This study aims to investigate the issues of academic literacy faced by students and lecturers during online learning. The sample of this study was 40 first-semester students from the University of Muhammadiyah Tangerang, Visual Communication Design study program. The instrument of the research is observation, interview, and document study based on student learning outcomes. In conclusion, the first result of this study indicates that the use of technological facilities has not been utilized optimally by students in the effort of improving their knowledge, self-awareness, creativity, and initiative to support their understanding and represent their academic literacy practice. The second result indicates that the facilities provided by the campus are not optimal to support students studying online, through the disclosure of university information that can be accessed at any time on the website, such as exam schedules, academic events, competitions, festivals, and other campus activities. The third result shows that students’ conversation practice during online learning can run well, due to clear instruction from the lecturer and conversation partners cooperatively